Restitution of Property and Religious Discrimination in Eastern Europe - Riegger, Maria (Refuge: Canada's Journal on Refugees, 2000)
This work centers on the religious libertysituation in Eastern Europe, includingcountries such as Hungary andRomania. The article discusses disputesover property rights and titles sincethe fall of communism, focusing onhow these have been closely interconnectedwith the religious backgroundand history of diferent ethnic groups.